(3GdecGaMI GdGMjGFjI dGeQGV JYaf MPhQ hPHhd fHGJGJ GdWeGWI HGSJJNOGe GdeGjchQGjRG GdeSJhWfI dLPhQ GdfHGJGJs - (3hMjO, GjGO bMWGf(B.s; (3YHhO, gGOi egOi(B.s; (3YHO Gddg, eGLO GHQGgje(B.s; (3cTeQ, MSjf fYjeI(B.s; (3Pfhf, Ydi MehO(B.s (2015)
(3gOaJ gPg GdOQGSI Gdi GdJMQi Yf aYGdjI YRdJjf ef GdeGjchQGjRG GdeSJhWfI dLPhQ GdfHGJGJ ai ecGaMI eQVi JYaf LPhQ hPHhd fHGJGJ GdWeGWI GdeJSHH Yf GdaWQjf GdeeQVjf (BRhizoctonia solani (3h (BFusarium oxysporum (3JMJ XQha GdHjJ GdeMei(B.s
(3jMJhi Ydi eQGLY(B.s
(3edNU HGddZI GdCfLdjRjI(B.s
1
Keywords: (3GdWeGWes -- (3CeQGV hBaGJs -- (3GdebGheI GdMjhjIs; (3JYaf GdLPhQs; (3eQV PHhd GdajhRGQjhe ai GdWeGWe(B.s